Temu Penguatan Keluarga dalam Upaya Memperbaiki Karakter Anak yang Berhadapan dengan Hukum (ABH) - Apriyanti Apriyanti; Nurhasan Nurhasan; Abdul Gafur; Endang Switri (Cv. Utility Project Solution, 2023)
The family environment is the main interaction in the formation of children's character. Parents have a very important role in raising and educating children by instilling good values. The purpose of carrying out this community service is to provide a deep understanding to parents and families in an effort to improve the character of children who are in conflict with the law. To achieve this goal, the methods carried out in this extension use lecture, discussion, and question and answer methods. The results obtained are that religious education taught in the family is the most important thing to improve the character of children who are in conflict with the law. Children's bad behavior is caused by the child's social environment, the necessities of life, and the mass media. Therefore, children need direction and guidance so that good character values ​​can be applied in everyday life. Exemplary parents and the environment, providing halal and good food, providing basic religious education, sufficient attention and praying to Allah swt with humility and hope are solutions that can be taken in an effort to improve children's character.